2018
DOI: 10.1186/s12913-018-3193-8
|View full text |Cite
|
Sign up to set email alerts
|

Reported use of evidence in clinical practice: a survey of rehabilitation practices in Norway

Abstract: BackgroundThe South Eastern Health Region in Norway serves approximately 2.8 million people, which is more than half of Norway’s population. Physical medicine and rehabilitation services are provided by 9 public hospital trusts and 30 private rehabilitation facilities. The purposes of this study were to conduct a psychometric analysis of the EBP Implementation Scale (EBPIS) and describe rehabilitation clinicians’ self-reported 1) use of evidence-based practices (EBPs), 2) use of EBPs across hospitals, and 3) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Although some studies have found significant associations between EBP and age [ 4 , 5 , 7 , 28 – 30 ], years of professional experience [ 4 , 25 , 31 33 ], working in a multidisciplinary team [ 29 ], number of people in the workplace [ 4 , 29 ], years of practice [ 7 , 25 , 32 , 33 ], and work settings [ 25 , 31 ], these variables did not show significant effects in the population of Spanish physiotherapists.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have found significant associations between EBP and age [ 4 , 5 , 7 , 28 – 30 ], years of professional experience [ 4 , 25 , 31 33 ], working in a multidisciplinary team [ 29 ], number of people in the workplace [ 4 , 29 ], years of practice [ 7 , 25 , 32 , 33 ], and work settings [ 25 , 31 ], these variables did not show significant effects in the population of Spanish physiotherapists.…”
Section: Discussionmentioning
confidence: 99%
“…Since CFA is preferred over EFA in the COSMIN methodology [ 31 ], only the results of CFA were rated in studies where both EFA and CFA were conducted. The quality of structural validity testing was rated as “very good” in 33 studies [ 36 38 , 40 , 42 44 , 47 , 49 , 50 , 53 , 55 , 72 , 74 , 75 , 77 , 79 81 , 84 , 86 , 88 , 90 , 92 , 94 , 97 – 100 , 105 , 106 , 110 ], “adequate” in 19 studies [ 39 , 45 , 48 , 51 , 52 , 57 , 58 , 60 , 62 , 69 , 76 , 89 , 91 , 95 , 108 , 109 , 111 ], “doubtful” in 9 studies [ 46 , 56 , 59 , 61 , 63 , 83 , 102 ], and as “inadequate” in two studies [ 66 , 73 ]. In both cases inadequate ratings were given due to low sample sizes [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…One factor. Factor loading > 0.70, Eigenvalue = 2.25 ( +) Low − 2 RoB EBP Implement [ 56 , 58 , 60 , 61 ] EFA. Disagreement about dimensionality between four studies.…”
Section: Resultsmentioning
confidence: 99%
“…At baseline, each participant completed an adapted version of the Evidence-Based Practice (EBP) Questionnaire ( 15 ), which has been used in clinical and knowledge translation studies ( 16 18 ). The questionnaire has several statements for which the participant indicates their level of agreement.…”
Section: Methodsmentioning
confidence: 99%